Does pronator quadratus repair affect functional outcome following volar plate fixation of distal radius fractures? A systematic review and meta-analysis - Ying, Liwei; Cai, Guoping; Zhu, Zhong; Yu, Guoliang; Su, Yongwei; Luo, Hua (Frontiers in Medicine, 2023)
Introduction The study aimed to evaluate the efficacy of pronator quadratus (PQ) repair versus no repair following volar plate fixation of distal radius fractures. Methods A comprehensive search was performed in PubMed, CNKI, EMBASE, Web of Science, Ovid, and Cochrane Library databases. All randomized controlled trials comparing PQ repair with no repair in distal radius fractures before January 2023 were included. Two investigators independently screened eligible articles, assessed the study quality, and extracted data from included studies. Continuous variables used standardized mean difference and 95% confidence interval as efficacy statistics. The meta-analysis was performed using the Revman 5.4 software. Results A total of 430 patients in 7 RCT studies were included in this meta-analysis, of which 218 underwent PQ repair, while 212 patients underwent no repair. The results of the meta-analysis displayed statistically significant differences in grip strength (short-term), pronation angle (short-term), and pronation strength (short- and long-term) between the two groups. No significant difference in other outcomes was found between the two treatment arms. Discussion The repair of PQ may further increase grip strength and pronation function in the short-term and enhance long-term pronator muscle strength compared to no repair. However, due to the small number of articles included in the study, the above conclusions need to be verified by a larger sample and multi-center clinical study.